Analisis Metode Ahe Pada Kemampuan Membaca Anak Usia Sekolah Dasar 6-7 Tahun Di Lembaga Bimbingan Belajar Yayasan Usman Baharun Ba’alawi Desa Bengkel - Saobah, Saobah; Hakim, Samsul; Hadlun, Hadlun (BALE LITERASI, 2025)
The great child method is a method of learning to read without spelling which has several steps in the learning process. This great child reading tutoring is a unique tutoring institution because this tutoring provides services to learn to read and write and count with 30 minutes per student with individual services not classical or group. The purpose of this study was to determine the analysis and to find out the implementation of the learning method of the great child on the reading ability of elementary school children aged 6-7 years at the tutoring institution of the Usman Baharun Ba'alawi Foundation, Bengkel Village. This research method uses descriptive qualitative methods. Data collection used through interviews, observation and documentation. The research instruments used observation guidelines, interview guidelines, documentation guidelines. The results showed that in the learning process of tutoring at the Usman Baharun Foundation Institution using the method of great child, it was quite fun for children and easier for children to accept because children were not required to memorise but just flowed through writing and playing so that children unconsciously mastered the lessons given. The conclusion shows that this research: The process of analysing reading activities for children aged 6-7 years at the Usman Baharun Ba'alawi Foundation tutoring institution using the great child method has a significant effect on improving children's reading skills, one of the supporting factors of reading activities for children aged 6-7 years at the Usman Baharun Ba'alawi Foundation tutoring institution, namely parents or guardians of students and the Bengkel village community feel enthusiastic about the presence of this institution